Benzoylation of polyphenylene oxide: characterization and gas permeability investigations - Bhole, Yogesh S.; Kharul, Ulhas K.; Somani, S. P.; Kumbharkar, S. C. (European Polymer Journal, 2005)
Benzoylation of polyphenylene oxide (PPO) was carried out with aromatic acid chlorides bearing specific groups at para-position (H methyl, Br, Cl and nitro), which differ in their polarity and bulk. The reaction conditions were optimized individually to get the high degree of substitution. These materials were characterized for thermal as well as other physical properties that are known to affect the gas permeation. In a series investigated, the nitrobenzoyl substitution on PPO resulted in the highest increase in glass transition temperature and the lowest thermal stability. An estimation of the packing density parameters-fractional free volume by density measurement and the d-spacing by X-ray diffraction analysis showed an increase in the packing density. The gas permeability was found to decrease in all the cases of benzoylation. The helium and oxygen based selectivities were increased, while CO2 based selectivities were decreased. The unusual trend observed in the gas permeation properties is explained on the basis of nature of substituent and the degree of substitution. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: benzoylation; Gas permeability; polyphenylene oxide; selectivity

Bimetallic nano alloy architecture on a special polymer: Ni or Cu merged with Pd for the promotion of the Mizoroki-Heck reaction and the Suzuki-Miyaura coupling - Patil, Vijay P.; Kashid, Abhijit A.; Solanki, Bhanupratap S.; Kharul, Ulhas K.; Iyer, Suresh (Journal of Chemical Sciences, 2021)
Novel Ni-Pd and Cu-Pd bimetallic nano alloys was designed and heterogenized on the highly robust ABPBI [poly(2,5-benzimidazole)] polymer in high yields using NaBH4 as reducing agent. These were versatile ligand free catalysts for the Mizoroki-Heck reaction and Suzuki-Miyaura coupling. The bimetallic Ni-Pd-ABPBI catalyst for the Mizoroki-Heck reaction of 4-iodo anisole could be recycled 5 times with high yields. Aryl bromides could also be activated for the Mizoroki-Heck reaction using Cu-Pd-ABPBI NP catalysts, with moderate yields. Graphic abstractSynopsis Novel bimetallic Ni-Pd and Cu-Pd nano alloys, heterogenized on the robust ABPBI [poly(2,5-benzimidazole)] polymer using NaBH4 as reducing agent, is described. These were versatile ligand free, noble metal conservative catalysts, for the Mizoroki-Heck reaction and the Suzuki-Miyaura coupling. Aryl bromides were activated for the Mizoroki-Heck reaction using the Cu-Pd-ABPBI catalyst.
Keywords: Bimetallic nano alloys; Cu-Pd-ABPBI; Mizoroki-Heck reaction; Ni-Pd-ABPBI; Suzuki coupling